THE EFFECT OF THE ADDITION OF BAMBOO LEAF ASH (BLA) AND LIME ON THE VALUE OF THE PLASTICITY INDEX ON THE STABILIZATION OF SOFT CLAY SOILS - Era Agita Kabdiyono; Alizar, Alizar; Ali Murdani (Jurnal Ilmiah Teknik, 2025)
Indonesia as an archipelagic country has many areas dominated by soft clay soils, such as along the eastern to southern regions of Sumatra Island, the northern side of Java Island, Kalimantan, and several other islands. In general, soil stabilization for construction purposes such as highways still relies on synthetic materials such as geotextiles. Therefore, an alternative to soil stabilization that is more environmentally friendly and economical is needed. This study aims to analyze the effect of the addition of Bamboo Leaf Ash (BLA) and lime on the value of the Plasticity Index (IP) in silent clay type soft clay in the context of road construction. The methods used include testing the physical properties of the original soil as well as the soil mixed with BLA and lime with a certain percentage. The results showed that the addition of BLA and lime had an effect on decreasing or increasing the value of the plasticity index, depending on the percentage of the mixture used. The highest IP value was achieved in the original soil mixture with 20% BLA and 5% lime at 14.241%, while the lowest value occurred in the mixture of 10% BLA and 5% lime which was 12.090%. Thus, the combination of BLA and lime can be an alternative soft clay soil stabilizing material to support more sustainable road construction.